1988
DOI: 10.1172/jci113566
|View full text |Cite
|
Sign up to set email alerts
|

Calcium dependency of prostaglandin E2 production in rat glomerular mesangial cells. Evidence that protein kinase C modulates the Ca2+-dependent activation of phospholipase A2.

Abstract: Calcium has been implicated as an important factor in prostaglandin production. Phospholipase A2, the enzyme believed to be rate limiting for prostaglandin synthesis, is stimulated by Ca2+; however, the levels of Ca2' necessary to stimulate phospholipase A2 in cell-free systems are higher than levels achieved in intact cells in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(49 citation statements)
references
References 39 publications
(21 reference statements)
3
46
0
Order By: Relevance
“…In this study, we have demonstrated that CERK-derived C1P is instrumental in the production of eicosanoids, corroborating our previous studies illustrating that siRNA downregulation of CERK blocks the release AA by inhibiting Eicosanoid synthesis in CERK ؊ / ؊ cells 1843 kinase C, which has been strongly linked to cPLA 2 ␣ activation (50)(51)(52)(53). This activation may or may not be dependent on C1P, and unpublished fi ndings from our laboratory show that a DAG lipase inhibitor is a dramatic stimulator of eicosanoid synthesis without the requirement of C1P.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, we have demonstrated that CERK-derived C1P is instrumental in the production of eicosanoids, corroborating our previous studies illustrating that siRNA downregulation of CERK blocks the release AA by inhibiting Eicosanoid synthesis in CERK ؊ / ؊ cells 1843 kinase C, which has been strongly linked to cPLA 2 ␣ activation (50)(51)(52)(53). This activation may or may not be dependent on C1P, and unpublished fi ndings from our laboratory show that a DAG lipase inhibitor is a dramatic stimulator of eicosanoid synthesis without the requirement of C1P.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the increase in plasmalogen-selective PLA2 during hypoxia measured in the absence or presence of calcium was confined to the cytosolic compartment with minimal change in membrane-associated activity. Accordingly, there is no significant translocation of enzyme activity, a characteristic of the human monocytic and rat kidney PLA2 enzyme activity using diacylglycerophospholipid substrates (21)(22)(23)(24)(25)(26)(27)(28). Although Ca2+ is not required for catalytic activity and calcium-dependent translocation does not occur, it is still possible that calcium-dependent mechanisms such as protein kinase C-mediated phosphorylation of PLA2 may play a role in the activation of cytosolic plasmalogen-selective PLA2 in rabbit proximal tubules during hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…The PKC inhibitor GF 109203x is known to be more selective for the ␣ isoform than for other PKC isoforms (80,81), suggesting the relevance of this isoform. A number of years ago, we had shown that agents that activate PKC could activate high molecular mass soluble PLA 2 activity in mesangial cells as long as there was an increase in [Ca 2ϩ ] i (82,83). Subsequent to the identification of this activity as cPLA 2 ␣, other investigators have reported that PKC is involved in the regulation of cPLA 2 ␣ (29, 31, 79, 84 -86).…”
Section: Role Of Constitutively Activated Erk1/2 On H 2 O 2 -Induced Aamentioning
confidence: 99%